Behaviour of RC beam repaired using alkali activated slag-based agent under static and cyclic loading. (June 2021) - Laskar, Sulaem Musaddiq; Mozumder, Ruhul Amin; Laskar, Aminul Islam
Abstract: Alkali activated materials have gained considerable popularity in construction industry. These materials have replaced conventional Portland cement in concrete either partially or fully. However, their use has been limited to primarily as a binding agent and little is known regarding its effectiveness as a repairing agent. In the present study, an attempt has been made to evaluate the potential of blast furnace slag-based alkali activated system as a concrete repairing agent. To serve this goal, reinforced Portland cement concrete beams were cast and subjected to varying level of damage by imparting static and cyclic loading. Blast furnace slag-based alkali activated paste and mortar were used to repair the damaged beams. Subsequently, repaired beams were tested in laboratory under static and cyclic loading condition. To evaluate the efficacy of alkali activated slag as repairing agent, test results were compared with that of Portland cement repaired specimens under identical damage and loading conditions. Criterion such as load carrying capacity, ductility, energy dissipation capacity and stiffness degradation were adopted to quantify the degree of success for each case. Laboratory based test results indicated that specimens repaired with alkali activated slag exhibited superior performance compared to identical specimens repaired with Portland cement systems w.r.t. all the parameters studied. The study also revealed that the level of damage significantly influenced the static and cyclic behavior of the repaired beams irrespective of repairing agent employed.